RELATIONSHIP BETWEEN SELF EFFICACY AND ADHERENCE TO FE TABLET CONSUMPTION AMONG ADOLESCENT GIRLS - Chalatha Doa, Nazatul Shima; Mediastuti, Fitriani; Revika, Era (Jurnal Manajemen Kesehatan Indonesia, 2024)
Anemia in adolescents can have an adverse impact on decreased immunity, learning concentration, fitness, and productivity. The provision of Fe tablets to adolescents is carried out as one of the interventions to reduce the prevalence of anemia. Adherence of adolescent girls in consuming Fe tablets is one of the indicators of the success of anemia prevention and control programs in adolescent girls. The high and low level of compliance to consuming Fe tablets in adolescents is due to several factors, one of which is self-efficacy. This study aims to determine the relationship between self-efficacy and adherence to taking Fe tablets in adolescent girls at SMPN 1 Sewon Yogyakarta. This study was conducted on 90 adolescent girls in class VII at SMPN 1 Sewon Yogyakarta. This study included quantitative research with analytic observational research type with a cross-sectional-study approach and using a simple random sampling technique. Data analysis was performed by univariate analysis using frequency distributions and percentages, and bivariate analysis using the chi-square test. The results showed that respondents who had a high level of self-efficacy amounted to 51.1%, while the low category amounted to 48.9%. In addition, the results of this study indicate that the level of compliance of adolescent girls in consuming Fe tablets at SMPN 1 Sewon Yogyakarta is mostly in the high category of 55.6%, while the low category is 44.4%. The results of data analysis using the chi-square test obtained a p-value of 0.000 using an alpha of 0.05, so the p-value <0.05. The results of this study can be concluded that there is a relationship between self-efficacy and adherence to taking Fe tablets in adolescent girls at SMPN 1 Sewon Yogyakarta. Keywords: Anemia, Self Efficacy, and Adherence to Taking Fe Tablets.